STOCK MARKET DEVELOPMENT IN CEE COUNTRIES – THE PANEL DATA ANALYSIS - Kurach, Radosław (Ekonomika, 2010)
Since financial system development is a necessary condition of the long-run economic growth, in this paper we address the question about the factors that may drive in particular the development of stock market segment. We propose a set of potential determinants and then empirically verify their importance, employing panel data methodology. We focus our attention on the thirteen CEE states and look for the conclusions that may be specific for transition economies in this region. Finally, we formulate the finding that large budget deficits have affected significantly and adversely the CEE countries’ stock markets growth. p>